Histological Study on Adventitious Root Formation in Stem Cuttings of Young Durian (Durio zibenthinus Murr.) Seedlings - Hasan, B. M.; Dood, P. B. (1989)
Cuttings obtained from young durian (Durio zibenthinus Murr.) seedlings rooted vel) Teadily. A histological study carried out on the rooting zone of these cuttings showed that cell walls of the derivative cells appeaTed relatively thin which probably is desirable fOT these cells to readily reven back to the undifferentiated state and ultimately become root primordia. It also showed that the stem had yet to develop any from of mechanical barrier that may restrict the development of adventitious roots.